Aplikasi Pemuasaan dan Pakan Fermentasi Terhadap Pertumbuhan dan Rasio Konversi Pakan Ikan Nila (Oreochromis niloticus) - Shadila, Tika Aprilia; Jubaedah, Dade (Seminar Nasional Lahan Suboptimal, 2024)
Shadila, T.A., & Jubaedah, D. (2024). Aplication of starvation and fermented feed on growth and feed conversion ratio of tilapia (Oreochromis niloticus). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 135–142). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).One of the methods that can increase the growth of culture tilapia is by applying a combination of the starvation method and feed fermentation. The results of previous studies showed a high increase in fish growth when fish are starvated and fed fermented feed compared to the growth of fish without starvated and fed non fermented feed. The purpose of this activity was to determine the growth and feed conversion ratio of tilapia (Oreochromis niloticus) that were starvated and fed fermented feed at Kelompok Pembudidaya Ikan in Tanjung Seteko, Indralaya, Ogan Ilir. Fish rearing for 28 days. Fish stocked in 2 nets (size 0,5 m ´ 0,5 m ´ 0,65 m) that were placed in concrete pond (size 5 m ´ 4 m ´ 0,7 m). The first pond (K0) as control (without starvation and fed by commercial feed) and the second pond (K1) as treatment (starvated and fed by fermented feed). The parameters were absolute growth of weight and length, feed conversion ratio, and survival rate. Water quality measurements were temperature and pH. The results showed that absolute growth of tilapia that were starvated and fed by fermented feed were higher than those were not starvated and fed by commercial feed. Fish that starvated and fed by fermented feed produced an absolute weight growth of 7.14 g, absolute length growth of 2.34 cm, feed conversion ratio of 1.4, survival rate of 93.3%, and water quality in fish ponds were pH of 7.3-8.3 and temperature of 25.4-31.7℃.